The Long Arm Of Welfare Retrenchment: How New Right Socio-Economic Policies In The 1980s Affected Contact With The Criminal Justice System In Adulthood - Gray, Emily (The British journal of criminology, 2022)
The socio-economic policies of the British ‘New Right’ administrations have been associated with increases in crime using aggregate data. This paper assesses if the trend remains when we test individual-level relationships using two British cohort studies (the National Child Development Study 1958 and the British Cohort Study 1970). Our results point to a set of long-term ‘period effects’ in which those reliant on the welfare state at specific time-points in the 1980 and 1990s (regardless of their age) were more likely to be drawn into the criminal justice system in adulthood (circa 2000). This paper considers (i) how British ‘New Right’ welfare policies may have had unintended, but lasting consequences for individuals in receipt of social security assistance and (ii) the interplay between micro and macro criminological analysis.